The pan-americanist imaginary and O Cruzeiro Internacional (1957-1965) - Meyrer, Marlise Regina (Revista Tempo e Argumento, 2016)
Abstract The article aims to identify the main ideas that supported the launch of the magazine O Cruzeiro Internacional (1957-1965), Brazilian journal published in Spanish and distributed throughout Latin America, Spain and areas of the United States. It tries to understand how these ideas have permeated the diffusion of a specific pan-American imaginary on certain groups and/or governments that guided through texts and photographic images a set of social representations on Latin America. These, in general, were selected for the defense of a Latin American unity under the economic, political and cultural hegemony of Brazil, at the regional level and the of USA worldwide. Keywords: Photojournalism – Latin America; O Cruzeiro Internacional; Journals - Brazil. Original title: O imaginário pan-americanista e O Cruzeiro Internacional (1957-1965).